An iron complex and its preparation method and application
The iron diphenylphosphonate complex synthesized through solvothermal reaction solves the problem of limited catalytic activity caused by the rapid electron-hole recombination of existing photocatalysts, and achieves efficient photocatalytic cracking of water hydrogen production, with excellent catalytic activity and stability.
Patent Information
- Application Number
- CN202210646451.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-08
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-06-08
AI Technical Summary
The existing photocatalysts have rapid photogenerating electron-hole recombination in the fields of photodegradation dyes and photocatalytic hydrogen production, which limits the catalytic activity and urgently needs to provide a new coordination polymer with higher photocatalytic properties.
The iron diphenylphosphonate complex was synthesized by solvothermal reaction, and the molar ratio of ferric chloride hexahydrate and diphenylphosphonate in anhydrous ethanol was 1:1 to 5, and the reaction conditions were optimized to obtain an iron complex with a fibrous morphology.
The prepared iron diphenylphosphonate complex exhibits excellent hydrogen production activity and stability in water photocatalytic cracking, especially under ultraviolet visible light irradiation, its catalytic performance is maintained at a hydrogen production efficiency of 97%.
Smart Images

Figure CN114957321B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysis, and in particular to an iron complex and a preparation method and application thereof. Background Art
[0002] Coordination polymers are usually composed of organic ligands and central ions. Compared with individual organic or inorganic components, coordination polymers can exhibit different chemical or physical properties. Due to their novel network topology and unique physical and chemical properties, coordination polymers have great practical value and development prospects in the application of catalysis, magnetism, adsorption, etc. A large number of studies have found that iron complexes of different valence states are widely used in flame retardancy, photoelectricity, catalysis, etc. The iron (III) complex of phenylphosphonic acid synthesized by Yang's research group has good flame retardant function and is a good flame retardant. The iron (III) complex with a 3D network topology prepared by Jin et al. has a strong photoelectric conversion ability and is a photoelectric conversion material with great potential. In addition, the iron (II) complex synthesized by the Saka group is a highly active catalyst with high catalytic performance for the oxidation of ethylene oxide.
[0003] With the development of photocatalytic technology and coordination chemistry, coordination polymers have been widely used as photocatalysts in the fields of photodegradation of dyes and photocatalytic hydrogen production. Most catalysts have the phenomenon of rapid recombination of photogenerated electrons and holes, which limits the catalytic activity to a certain extent. At present, there is an urgent need to provide a new coordination polymer with higher photocatalytic performance. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an iron complex and a preparation method and application thereof.
[0005] In the first aspect, the preparation method of the iron complex provided by the present invention comprises: dissolving an iron salt and diphenylphosphonic acid in a solvent, and performing a solvothermal reaction; the iron salt is ferric chloride hexahydrate, and the molar ratio of the iron salt to the diphenylphosphonic acid is 1:1 to 5. The synthesis method of the present invention is simple, the reaction conditions are mild, the raw materials are easily available, and the preparation can be made from basic chemical raw materials. In particular, the present invention uses diphenylphosphonic acid as a ligand and iron as a coordination center ion to synthesize a diphenylphosphonic acid iron complex by solvothermal method, uses the diphenylphosphonic acid iron complex as a photocatalyst, and evaluates its photocatalytic performance by photocatalytic water splitting to produce hydrogen. The iron complex prepared by the present invention has excellent photocatalytic water splitting hydrogen production activity and stability.
[0006] Preferably, the molar ratio of the iron salt to the diphenylphosphonic acid is 1:2 to 4, and preferably, the molar ratio of the iron salt to the diphenylphosphonic acid is 1:3. In the present invention, by optimizing the ratio of the iron salt to the diphenylphosphonic acid, a diphenylphosphonic acid iron complex with excellent photocatalytic performance can be obtained within a preferred range.
[0007] More preferably, the solvent is anhydrous ethanol.
[0008] The present invention uses the above-mentioned proportion of ferric chloride hexahydrate, diphenylphosphonic acid and anhydrous ethanol as solvents, which is more conducive to the preparation of a fibrous iron diphenylphosphonate complex having a specific morphology and better photocatalytic water splitting hydrogen production activity and stability.
[0009] Preferably, the temperature of the solvent thermal reaction is 170-190° C., and the reaction time is 70-75 hours. The present invention can improve the morphology of the iron diphenylphosphonate complex and further improve the activity and stability of photocatalytic water splitting to produce hydrogen by optimizing the solvent thermal reaction conditions.
[0010] More preferably, the temperature of the solvent thermal reaction is 180° C. and the reaction time is 72 h.
[0011] Preferably, the method for preparing the iron complex further comprises mixing ferric chloride hexahydrate, diphenylphosphonic acid and anhydrous ethanol, and stirring at room temperature for 5 to 40 minutes, preferably 15 to 25 minutes.
[0012] Further preferably, the preparation method of the iron complex comprises the following steps: mixing hydrated ferric chloride, diphenylphosphonic acid and anhydrous ethanol and stirring; maintaining the mixture at a constant temperature of 175 to 185° C. for 70 to 73 hours to carry out a solvent thermal reaction; cooling to room temperature, filtering, washing and drying to obtain the iron complex.
[0013] In a second aspect, the iron complex provided by the present invention is obtained by the preparation method of the iron complex.
[0014] Preferably, the chemical formula of the iron complex is FeC 36 H 30 P3O6.
[0015] More preferably, the iron complex has a fibrous morphology, a smooth surface and uniform distribution, and a diameter of 0.5 to 3 μm. The specific iron complex provided in the present invention has better catalytic water splitting hydrogen production activity and stability.
[0016] In a third aspect, the photocatalyst provided by the present invention includes the iron complex obtained by the preparation method of the iron complex or the iron complex.
[0017] In a fourth aspect, the present invention provides an iron complex obtained by the method for preparing the iron complex or the use of the iron complex as a photocatalyst in a photocatalytic reaction.
[0018] More preferably, the method includes use in producing hydrogen by photocatalytic cracking under ultraviolet and visible light irradiation.
[0019] The beneficial effects of the present invention are at least that: the present invention adopts a solvent thermal synthesis method which is easy to operate, the synthesis method is simple, the reaction conditions are mild, the raw materials are easily available, and the diphenylphosphonic acid iron complex can be prepared using basic chemical raw materials. The iron complex has excellent photocatalytic water splitting hydrogen production activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. It is obvious that the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 The synthesis reaction equation of the iron complex provided in the embodiment of the present invention;
[0022] Figure 2 The SEM image of FeDPPA provided in the embodiment of the present invention;
[0023] Figure 3 The XRD spectrum of FeDPPA provided in the embodiment of the present invention;
[0024] Figure 4 A Fourier transform infrared spectrum of FeDPPA provided in an embodiment of the present invention;
[0025] Figure 5 (a) XPS broad spectrum of FeDPPA and (b) high-resolution spectrum of Fe 3d provided in the embodiments of the present invention;
[0026] Figure 6 (a) UV-visible diffuse reflectance spectra of DPPA and FeDPPA and (b) band gap spectrum of FeDPPA provided in the embodiments of the present invention;
[0027] Figure 7 TG graph and DTG graph of FeDPPA provided in the embodiment of the present invention;
[0028] Figure 8 (a) FeDPPA catalytic hydrogen production diagram under ultraviolet visible irradiation and (b) FeDPPA photocatalytic hydrogen production cycle reaction diagram provided in the embodiments of the present invention;
[0029] Fig. 9 Infrared spectra of (a) FeDPPA before photocatalytic hydrogen production and (b) after photocatalytic hydrogen production provided in an embodiment of the present invention;
[0030] Fig.10Schematic diagram of photocatalytic hydrogen production of FeDPPA under ultraviolet visible light irradiation provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The following embodiments are used to illustrate the present invention, but are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are followed. The implementation conditions in the embodiments can be further adjusted according to specific experimental conditions or factory conditions, and the implementation conditions that are not specified are generally the conditions in conventional experiments. The materials, reagents, etc. used in the following embodiments, unless otherwise specified, can all be obtained from commercial channels.
[0032] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.
[0033] Example 1
[0034] This embodiment provides an iron complex, the synthesis of which comprises the following steps:
[0035] (1) Ferric chloride hexahydrate FeCl3·6H2O (0.0860 g, 0.5 mmol) and diphenylphosphonic acid DPPA (0.2173 g, 1.5 mmol) were dissolved in 7 mL of anhydrous ethanol, and the mixture was stirred at room temperature for 20 min until it was homogeneous.
[0036] (2) The mixture was transferred into a 15 mL polytetrafluoroethylene-lined stainless steel autoclave, and the autoclave was placed in a muffle furnace. The autoclave was kept at a constant temperature of 180° C. for 72 h.
[0037] (3) After the reaction time is over, the autoclave is taken out and cooled naturally to room temperature. The autoclave is opened, filtered, washed with anhydrous ethanol, and dried in air to obtain a white sample (ferric diphenylphosphonate), which is labeled as FeDPPA. Elemental analysis data of FeDPPA: theoretical value C 61.12, H 4.27, actual value C 61.10, H 4.32.
[0038] Example 2
[0039] Characterization of the iron complex of the present invention
[0040] First, the morphology of FeDPPA in Example 1 was analyzed using a scanning electron microscope (SEM). Figure 2 As shown, the complex has a fibrous morphology, a smooth surface and uniform distribution, and a diameter range of about 0.5 μm to 3 μm.
[0041] FeDPPA was determined by X-ray diffraction (XRD). Figure 3 It can be seen that the complex is a crystalline compound, and there is a strong diffraction peak at 2θ=7.16°, which is attributed to the characteristic diffraction peak of metallic iron diphenylphosphonate.
[0042] In order to further determine the chemical composition of FeDPPA, infrared absorption spectra were performed. Figure 4 It can be seen that at 3055cm -1 and 1593cm -1 There is a strong absorption peak at 1437cm -1 There is a strong absorption peak at 1062cm, which is the characteristic absorption peak of the vibration of the benzene ring skeleton; -1 There is a strong absorption peak at , which is the characteristic absorption peak of Fe-OP. Therefore, the characteristic absorption peak on the infrared absorption spectrum further confirms the existence of important functional groups in the composition and structure of FeDPPA.
[0043] Based on the infrared absorption spectrum analysis, FeDPPA was tested by XPS to further study the bonding mode of each element in the complex. The XPS wide spectrum data of FeDPPA showed ( Figure 5 a), the complex contains four elements: C(1s), P(2p), O(1s) and Fe(2p). In the Fe 2p high-resolution spectrum of FeDPPA ( Figure 5 b), the binding energy peaks of Fe 2p3 / 2 and Fe 2p1 / 2 are 712.3 and 725.9 eV, respectively, and the spin-orbit separation energy between the two peaks is 13.6 eV. This result shows that Fe is present in FeDPPA as Fe 3+ exists in chemical form.
[0044] Example 3
[0045] Characterization of optical properties of the iron complex of the present invention
[0046] The optical properties of FeDPPA of Example 1 were studied by UV-Vis DRS. Figure 6 As shown, the absorption of diphenylphosphonic acid and FeDPPA is mainly located in the ultraviolet region, and their absorption edges in the ultraviolet region are at 315nm and 366nm respectively. By using the Tauc equation (αhν=A(hν-Eg) 2 ) and the UV-visible absorption data of the compound by making (αhν) 1 / 2 By tangent to the curve and extending it to the x-axis, the band gap value of the complex can be determined. Using this treatment, the band gap value of FeDPPA was determined to be 3.38 eV.
[0047] Example 4
[0048] Thermal behavior analysis of the iron complex of the present invention
[0049] The thermal behavior of FeDPPA in Example 1 was analyzed by thermogravimetry. Figure 7 As shown in the figure, there is an obvious weight loss interval on the TG curve of FeDPPA, which can be attributed to the decomposition of the organic components in the complex. The maximum weight loss rate and the highest weight loss temperature of FeDPPA in this weight loss interval are 3.65% / min and 486℃, respectively. At 700℃, the total weight loss and residual amount of FeDPPA are 58.37% and 41.63%, respectively. It can be seen that FeDPPA has excellent thermal stability in N2 atmosphere.
[0050] Example 5
[0051] Study on the photocatalytic performance of the iron complex of the present invention
[0052] Under ultraviolet visible light irradiation, the catalytic performance of FeDPPA in Example 1 was studied by photocatalytic water splitting to produce hydrogen. After irradiation with ultraviolet visible light for 3 hours, the hydrogen production of FeDPPA was 111.4 μmol / g ( Figure 8 a); The cycle performance test results show that FeDPPA still maintains a relatively stable hydrogen production capacity after 4 cycles of 12h, and the hydrogen production efficiency remains at 97% ( Figure 8 b).
[0053] The stability of FeDPPA photocatalytic water splitting to produce hydrogen was evaluated by infrared absorption spectroscopy. The FT-IR spectra of FeDPPA before and after photocatalytic hydrogen production under ultraviolet visible light irradiation are shown in Figure 1. Fig. 9 As shown in the figure, the spectrum of FeDPPA remains basically unchanged before and after photocatalytic hydrogen production, indicating that FeDPPA has good stability. In addition, no new peaks appear in the infrared spectrum, indicating that FeDPPA does not form new functional groups before and after photocatalysis.
[0054] Example 6
[0055] Analysis of the photocatalytic mechanism of the iron complex of the present invention
[0056] Based on the above test characterization and analysis, the possible mechanism of photocatalytic water splitting and hydrogen production of the above-mentioned complex FeDPPA was proposed ( Fig.10). In the process of photocatalytic water splitting to produce hydrogen, there is a mechanism of electron transfer from the ligand to the metal. The specific process is as follows: Under the irradiation of ultraviolet visible light, the benzene ring on diphenylphosphonic acid absorbs photons to produce photogenerated electrons and holes. The electrons on the benzene ring of diphenylphosphonic acid are transferred to Fe(III) to form Fe(II). At the same time, the holes are captured by the sacrificial agent triethanolamine. Fe(II) has a high reactivity and can undergo a redox reaction with H2O to generate H2, thereby completing the photocatalytic water splitting reaction to produce hydrogen.
[0057] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. An application of an iron complex in photocatalytic water splitting to produce hydrogen, characterized in that: The preparation method of the iron complex comprises: dissolving ferric chloride hexahydrate and diphenylphosphonic acid in anhydrous ethanol, and performing a solvent thermal reaction; the molar ratio of the ferric chloride hexahydrate to the diphenylphosphonic acid is 1:3; the temperature of the solvent thermal reaction is 180°C, the reaction time is 72 hours, and the chemical formula of the iron complex is FeC 36 H 30 P3O6.
2. The use of the iron complex according to claim 1, characterized in that: The method for preparing the iron complex further comprises mixing ferric chloride hexahydrate, diphenylphosphonic acid and anhydrous ethanol, and stirring at room temperature for 5 to 40 minutes.
3. The use of the iron complex according to claim 2, characterized in that: The method for preparing the iron complex further comprises mixing ferric chloride hexahydrate, diphenylphosphonic acid and anhydrous ethanol, and stirring at room temperature for 5 to 25 minutes.
4. The use of the iron complex according to any one of claims 1 to 3, characterized in that: The preparation method of the iron complex comprises the following steps: mixing hydrated ferric chloride, diphenylphosphonic acid and anhydrous ethanol, and stirring; maintaining the mixture at a constant temperature of 180° C. for 72 hours to perform a solvent thermal reaction; cooling the mixture to room temperature, filtering, washing and drying the mixture to obtain the iron complex.
5. The use of the iron complex according to any one of claims 1 to 3, characterized in that: The iron complex has a fibrous morphology, a smooth surface and uniform distribution, and a diameter of 0.5-3 μm.
6. A method for producing hydrogen by photocatalytic cracking, characterized in that: Under the irradiation of ultraviolet and visible light, the iron complex in any one of claims 1 to 5 is used as a photocatalyst to produce hydrogen by photocatalytically splitting water.
Citation Information
Patent Citations
Flame retardance and smoke suppression type PVC (polyvinyl chloride) composite material and preparation method thereof
CN109467845A